(untitled) (Olhar de Professor, 2021)
The inclusion of children with disabilities in mainstream education is a subject that has sparked several discussions. It is essential to consider the way teachers assess the learning process of their students for the success of the inclusive process and to face hardships. Therefore, the goal of this study is to look upon the assessment process of mainstreamed children with disabilities and how teachers are able to handle the teaching and learning process for their assessment to respect the rhythm and specific features of each student. To this end, we performed a review for literature published between 2018 and 2019, and the collection of data from the periodicals from the area of Education and Chemistry and sub-area Special/Inclusive Education, by access through the Fundação de Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (Coordination for the Improvement of Higher Education Personnel, Capes) website, available in the Federal University of Fronteira Sul (UFFS), and of scientific periodicals with an A1 and A2 Qualis score, using the keywords Inclusive Education, Assessment, Teacher Education, and Deaf Education. In order to build the analyses, the Análise Textual Discursiva (Discursive Textual Analysis) by Moraes and Galiazzi (2011), which revealed that many studies are still needed. As this study unfolded, we opted to filter the perception of teachers in Inclusive Education as to assessment and the teaching process in regular education, which shows the need for teacher education courses to discuss the subject in formative processes. In this sense, to discuss the assessment and the teaching process of students with disabilities and that have difficulties, demands the consideration of early education to reinforce a just, equal and righteous inclusive process.